Deterministic Kalman Filtering on Semi-Infinite Interval - L. Faybusovich; T. Mouktonglang (International Journal of Mathematics and Mathematical Sciences)
We relate a deterministic Kalman filter on semi-infinite interval to linear-quadratic tracking control model with unfixed initial condition.